Nussbaum’s Concept of Cosmopolitanism: Practical Possibility or Academic Delusion? - Naseem, M. Ayaz; Hyslop-Margison, Emery James (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2006)
In this paper, we explore Martha Nussbaum’s version of cosmopolitanism and evaluate its potential to reduce the growing global discord we currently confront. We begin the paper by elucidating the concept of cosmopolitanism in historical and contemporary terms, and then review some of the major criticisms of Nussbaum’s position. Finally, we suggest that Nussbaum’s vision of cosmopolitanism, in spite of its morally noble intentions, faces overwhelming philosophical and practical difficulties that undermine its ultimate tenability as an approach to resolving international conflict.